Detection, cerebrovascular complications and risk factors associated with vertebrobasilar dolichoectasia: a scoping review - Morales-Verdugo, Juan; Pérez-Rojas, Francisco; Figueroa-Figueroa, Alan; Lagos-Fica, Javier; Vera-Paredes, Joaquín; García-Suárez, Olivia; Cabezas-Salgado, Juan; Orellana-Cortés, Félix (Frontiers in Neurology, 2025)
IntroductionVertebrobasilar dolichoectasia, a condition characterized by increased length, volume, and curvature of vertebrobasilar system, has been linked to an increased risk of cerebrovascular diseases. However, the evidence on its morphological components and risk factors for these diseases is contradictory. The lack of consensus about its characteristics, detection, cerebrovascular complications, or risk factors highlights the need for a review that synthesizes this information. Therefore, the purpose of this study was to analyze and synthesize the literature on diagnostic and detection criteria, risk factors and cerebrovascular complications associated with vertebrobasilar dolichoectasia.MethodsA scoping review was conducted following the PRISMA-ScR statement. The search was carried out in Web of Science, PubMed, and Scopus. Data on adult population with a confirmed diagnosis of vertebrobasilar tortuosity or dolichoectasia through computed tomography or magnetic resonance imaging compared with a control group were included, and excluding studies whose participants presented another neurological pathology coexisting with the cerebrovascular disease. The information was extracted, evaluated, and synthesized to provide a concrete view of the current evidence. Additionally, methodological quality was assessed with the Newcastle-Ottawa scale.ResultsOf 1,373 identified studies, 18 met the eligibility criteria, including 3,058 participants (1,055 cases and 2003 controls). Vertebrobasilar dolichoectasia components, independently or associated with cardiovascular risk factors such as hypertension, atherosclerosis, diabetes, or smoking, are associated with a higher risk of cerebrovascular disease, mainly in the posterior circulation, affecting brain regions as brainstem, cerebellum, thalamus and occipital cortex.ConclusionThe findings suggest an increased risk of cerebrovascular disease when vertebrobasilar dolichoectasia or its components are present. More studies are necessary to quantify the risk of dolichoectasia components in different types of cerebrovascular disease.